Hematopoietic progenitor cell transplantation in multiple myeloma - Goldschmidt, Hartmut; Hegenbart, Ute; Haas, Rainer; Hunstein, Werner (Onkologie, 1995)
The median survival of conventionally treated patients with multiple myeloma is 3 years. Modifications of conventional chemotherapy and the administration of interferon-α have failed to show an improved survival in most randomized trials. Therapy with dose-escalated alkylating agents (i. e. melphalan 140 mg/m2) induced higher remission rates than conventional treatment. If followed by allogeneic or autologous hematopoietic progenitor cell transplantation, the hematotoxicity of the described dose-escalated treatment could be reduced. Results of transplantation trials are summarized and discussed. The transplantation of autologous peripheral blood progenitor cells results in a faster hematopoietic reconstitution and a decreased high-dose therapy-related morbidity compared to autologous bone marrow and should therefore be preferred. Although the randomized French myeloma trial showed a significant survival advantage for patients following autologous transplantation, further randomized prospective studies are required to evaluate the role of blood progenitor cell transplantation after high-dose treatment in multiple myeloma. Prognostical factors and future treatment modalities for myeloma are discussed.
Elektronische Reproduktion der Druck-Ausgabe 11. Mai 2009
Gesehen am 15.05.2025